National-, institutional-, and individual-level determinants of dental research excellence: an analysis of Stanford–Elsevier lists of the top 2% scholars worldwide (2017–2023) - Riad, Abanoub (Frontiers in Oral Health, 2025)
BackgroundResearch excellence, distinct from productivity, is a key criterion in science policy and institutional evaluation. This study examined global distribution and determinants of dental research excellence using the Stanford–Elsevier Lists (SEL) of the top 2% most-cited scientists.MethodsA bibliometric analysis was conducted using SEL datasets from 2017 to 2023. The analysis followed an ecological model consisting of three layers of independent variables: national-level indicators (macroeconomic metrics, oral disease burden, and development indices), institutional rankings, and individual-level variables (gender and academic age) were analysed. Descriptive statistics, multivariable regressions, and mixed-effects models were applied.ResultsThe analysis demonstrated a markedly uneven global distribution of excellent dental scholars (EDS), with 96.1% and 88.9% of career-long and single-year EDS, respectively, based in high-income countries. English-speaking countries dominated, reflecting historical and linguistic biases. Institutional elitism was apparent, with 20 universities accounting for nearly one-fifth of all EDS worldwide. Gender disparities persisted, with women comprising only 14.8% (career-long) and 18.1% (single-year). Academic age consistently predicted scholarly metrics more strongly than gender. EDS numbers correlated positively with macroeconomic indicators, particularly R&D investment, while oral disease burden was negatively correlated.ConclusionsDental research excellence is disproportionately concentrated in high-income, English-speaking countries and elite institutions. Historic gender disparities remain, though narrowing trends are noticeable. The observed misalignment between oral disease burden and research excellence highlights the need for inclusive, needs-based research investment.